Knowledge, Attitude, Practice of Hand Hygiene among Dental Students in Tertiary Care Teaching Hospital Khammam Telangana - Swathi, G.; Pratap, K. V. N. R.; Madhavipadma, T.; Singh, Surbhit; Srujankumar, V.; Mudigonda, Harsha (International Journal Of Drug Research And Dental Science, 2025)
This study aims to investigate the knowledge, attitude, and practice of hand hygiene among dental students. We can access the level of knowledge among students about the importance of hand hygiene, and proper hand washing techniques, by which we can determine whether they possess up-to-date knowledge about hand hygiene or not. We can access the attitudes and perceptions towards hand hygiene by knowing their beliefs, values, and opinions about the importance of hand hygiene in preventing the spread of infection. Practice will determine whether students are adhering to proper hand hygiene protocols, in real-world clinical settings or not.Aim: to assess the hand hygiene compliance rate among dental students in tertiary dental clinics.ObjectivesTo evaluate the level of knowledge of dental students about various hand hygiene protocols.To determine dental students' perceptions and attitudes towards hand hygiene, including its importance in preventing the spread of infections.To assess dental students' actual hand hygiene practices in clinical settings.Method: A cross-sectional survey was conducted among 265 dental students, comprising 114 males (54.3%) and 121 females (45.6%), including 56 first-year BDS students, 76 second-year BDS students, 50 third-year BDS students, 53 final-year BDS students, and 30 interns. The survey included 15 questions exploring awareness, and perceptions, of hand hygiene among dental students. Responses were analyzed based on gender and year of Study using chi-square tests to identify statistically significant differences.